2012
DOI: 10.1007/s13191-012-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Post exposure prophylaxis to occupational injuries for general dentist

Abstract: Occupational injuries which expose health-care professionals to blood-borne pathogens continue to be an important public health concern. Especially, dentists are at increased risk of exposure to Hepatitis B, Hepatitis C, and HIV. Dentists should remember and apply many precautions to prevent the broad spectrum of sharps and splash injuries that could occur during the delivery of dental care. This article updates and consolidates recommendations for the management of dental health-care personnel who have occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…After a needlestick incident, patient risk factors should be evaluated, and blood samples collected for HBV, HCV, and HIV testing. Consent should be obtained before testing for HCV and HIV, followed by a decision on administering post-exposure prophylaxis (PEP) [40]. Exposed individuals should be referred to qualified providers for counseling, risk assessment, and consideration of antiretroviral drugs or hepatitis B vaccine [39,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…After a needlestick incident, patient risk factors should be evaluated, and blood samples collected for HBV, HCV, and HIV testing. Consent should be obtained before testing for HCV and HIV, followed by a decision on administering post-exposure prophylaxis (PEP) [40]. Exposed individuals should be referred to qualified providers for counseling, risk assessment, and consideration of antiretroviral drugs or hepatitis B vaccine [39,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A needle-stick injury or scalpel injury on the stabilizing fingers could transmit microbiomes such as hepatitis B virus, hepatitis C virus, and HIV from the patient to the surgical team members. 38 , 39 The dentist and the assistants must exercise with caution throughout the surgical procedure to prevent such events. Several studies have demonstrated the efficacy of double gloving on reducing the perforation of inner gloves and the risk of cross-contamination.…”
Section: Stabilization With Fingers and Gauzementioning
confidence: 99%
“…Furthermore, different challenges are faced by the dentists such as restricted field of vision and sudden patients’ movement during the use of needle or sharp instruments. These challenges make the dentist vulnerable to exposure [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent reports by the WHO, occupational exposures cause about 40% of Hepatitis B virus (HBV) and Hepatitis C virus (HCV) worldwide, with Human Immunodeficiency virus (HIV) accounting for 2.5% of infections among HCWs. Correspondingly, chronic cases of HCV, and HBV are also on the rise with over, 200 M chronic HCV carriers, and 350 to 400 M chronic HBV carriers globally [ 2 , 7 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation